Optimasi Vektor Bobot Learning Vector Quantization Menggunakan Algoritme Genetika untuk Penentuan Kualitas Susu Sapi - Karina Widyawati; Budi Darma Setiawan; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Milk has a complete nutrition that important for body so every people can consume milk with high quality. Determination of milk quality can by tools called Milkoscope Julie c2 or Lactoscan to test the chemical contents. That tools can identified the chemical content which includes 7 parameters. From 7 parameters, 3 parameters are provisions of SNI and 4 parameters are not listed in porvisions of SNI. If we determine milk quality only from 3 parameter in SNI, the result is not the best. Based on that problems, we need a system that can help us to determine quality of milk considering 7 parameters. Method that can be used for this problem is Learning Vector Quantization (LVQ) but LVQ need an optimazion method to produce the best weight vector and increase accuracy using Genethic Algorithm (GA). Best weight vector of GA will be used for LVQ training and the latest wight vector of training used for testing. The result of this research obtained the highest accuracy average is 88% with best parameters such as population size 30, crossover rate 0,5, mutation rate 0,5, generation 75, alpha 0,6, and alpha decrement 0,3.